Requirement of Postoperative Ventilation and analgesics during Off-Pump Coronary Artery Bypass (OPCAB) surgery – A Comparison between Combined High Thoracic Epidural Anaesthesia (HTEA) with GA and GA Alone (Bangladesh Heart Journal, 2021)
Beckground: This is often difficult to achieve optimal pain relief after coronary artery bypass surgery and also great challenge to choice appropriate analgesics with minimize the duration of mechanical ventilation. In the postoperative period inadequate analgesia may increase morbidity by causing adverse haemodynamic, metabolic, immunologic and haemostatic attentions and prolong mechanical ventilation with more ICU stay. High Thoracic Epidural Anaesthesia (HTEA) as an adjunct to general anaesthesia has been shown to be potentially beneficial in postoperative pain relief and the requirement of mechanical ventilationin patients with off-pump coronary artery bypass surgery (OPCAB). HTEA provides good protection from stress response, ensures hemodynamic stability, improves distribution of coronary blood flow with reducing demand of oxygen, less requirement of postoperative analgesia , mechanical ventilation and ICU stay.Objective: This study has been undertaken with a view to compare requirement of postoperative mechanical ventilation and analgesics in OPCAB surgery between HTEA with GA and GA alone.Methods: This prospective, randomized case control comparative study was carried out in sixty patients without having left main coronary artery disease, left ventricular ejection fraction